Proposing regulatory-driven blue finance mechanism for blue economy development - Nagisa Yoshioka; Hsing Hao Wu; Michael C. Huang; Hajime Tanaka (Asian Development Bank Institute (ADBI), 2020)
The ocean is being jeopardized because of the adverse effects of climate change and human activities, such as marine plastic pollution, extreme weather events, sea level rises, and others. In addressing these ocean risks, ensuring sufficient finance to sustain the ocean economy is an ever-present challenge, particularly for those vulnerable regions, coastal communities, and small island developing states. Blue Finance, as a concept, is thus critical to ensure sustainability and conservation of the marine ecosystem and resources aligned with economic growth. Ocean sustainability has attracted global finance initiated by multilateral development banks and international institutions. This paper explores the interconnection between stakeholders among agents in the Blue Finance mechanism to illustrate incentives to increase private investment in addition to public donations in financing ocean health protection and boosting the blue economy. We then attempt to propose potential regulatory and institutional arrangements incorporating the concept of the blue financing principles in the context of the relevant legal regimes concerning marine governance both at the international and domestic levels. We further elaborate on the potentials of these legal and institutional arrangements to provide incentives for increasing private investment in marine development programs seeking economic growth and sustainability.
Keywords: G28; K33; O44; 330; Blue Finance; blue economy; climate change; ocean sustainability; ocean and coastal resilience